My Sister Haunts me: Sororal Spectres and the "Otherness" of Female Sexual Desire in the Mid-Nineteenth Century Ghost Story. Issue 4 (2nd October 2021) - Snailham, Fiona
ABSTRACT: The ghost, in its very essence, is "Other". It sits on the boundaries between life and death, reminding the living of the actuality of their existence and challenging their perceptions of the permanence of self. Applying Hegel's model of intersubjectivity to depictions of feminine phantoms, this essay explores women's ghost stories as representations of, and commentary on, the "otherness" of women's sexuality in the mid-nineteenth century. Focusing on the centrality of the sororal relationship in supernatural fiction by Elizabeth Gaskell and Eliza Lynn Linton, the paper considers sorority as a narrative device through which texts explore, reflect and possibly embed ideologies surrounding female sexual desire.